No Trouble: A Reply to Wielenberg - Craig, William Lane (TheoLogica, 2021)
Eric Wielenberg's two alleged contradictions in my view of God, time, and creation are easily resolved. The first is dissolved by appreciating that God's power to create the universe is a modal property which God may possess even if He never in fact exercises that power. The second contradiction evaporates once one adopts a relational view of time.